(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2025)
One of the most salient features of Islamic Sharia is its dynamic equilibrium of flexibility and constancy, endowing it with perennial relevance and applicability across all epochs and locales. Such a trait could not be sustained without the intrinsic capacity for evolution, underscoring its adaptability, and facilitating its alignment with the varying conditions and exigencies of the individuals bound by its directives. This transformative aspect is pertinent to the juridical decrees that are contingent upon change, recognizing that while certain tenets in Sharia remain immutable, steadfast against the tides of time and space, others are amenable to modification in response to shifting circumstances. KEYWORDS: Fatwa; Migration; Location; the Characteristics of Islamic Sharia; Flexibility